The melamine milk crisis in China - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case concerns the business ethics of companies who knowingly put their customers in danger in order to make greater profits. Using the example of the Sanlu Group in China, which added dangerous melamine to its milk products, this case also asks what the responsibility of international firms is to police their partners.